Rural-urban food, nutrient and virtual water flows in selected West African cities - Drechsel, Pay; Graefe, Sophie; Fink, M. (International Water Management Institute, 2007)
Impacts of increasing population pressure on food demand and land and water resources have sparked interest in nutrient and water balances and flows at a range of scales. In IWMI Research Report 115, it was tried for the first time to quantify rural-urban food flows for selected cities in Ghana and Burkina Faso to analyse their dependency on food supplied from rural vs. peri-urban vs. urban farming. Both, the urban nutrient and water footprints are closely interlinked. Currently, 80-95 percent of the domestic water used and the nutrients consumed go to waste without treatment or resource recovery. The economic dimensions are significant. Options to reduce the environmental burden by closing the rural-urban water and nutrient cycles are discussed.